Diagnóstico del Clima Organizacional en el Gobierno Autónomo Descentralizado del Cantón Zapotillo año 2022. - Requena Rogel, Lady Jeraldine (2023)
The objective of this research is to carry out a diagnosis of the organizational climate at the Decentralized Autonomous Government of Zapotillo canton through the year 2022. There was a study population of 158 public servants, of which 157 public servants were surveyed and only the mayor of the GAD was interviewed. To determine the results of the surveys and interviews, various methods were applied, including inductive, deductive, analytical, and synthetic approaches. In addition to using the survey questionnaire of the researchers Koys & Decottis, (1991), surveys were applied and evaluated using the Likert scale response format. In the results obtained, an adaptation of the Technical Norm for the Measurement of Work Climate of the Public Service of the Ministry of Labor (2018) was conducted. Research techniques were applied to determine the organizational climate of the entity, and it was determined to be 3.43 out of 5, which is a very good score, indicating a very good work environment and high levels of satisfaction, but there are certain subfactors that can be improved. It also has the improvement plan of the 8 factors that require attention to reach excellence and promote a good organizational climate within the entity, their respective conclusions, recommendations, bibliography and annexes.